P35. Cortico-striatal functional connectivity in Huntington's disease measured with high-field functional MRI: A biomarker for disease progression?. Issue 8 (August 2018) - Kronenbürger, M.; Hua, J.; Xinyuan, M.; Unschuld, P.; van Zijl, P.; Ross, C.
Abstract : Background: Huntington's disease (HD) is a progressive neurodegenerative disorder caused by CAG expansion in the Huntingtin gene. HD manifests by involuntary movements, cognitive and behavioral changes. The approximate time-to-onset can be predicted from the length of CAG repeat in HD subjects, which allows for the identification of subjects in the pre-manifest stage of HD, who do not have symptoms or structural brain changes (atrophy). Disease modifying treatment may have special value if it is initiated in the premanifest stage of HD, before structural brain changes occur. Aim: Cortico-striatal functional connectivity may be altered in HD many years before symptoms onset. Thus cortico-striatal functional connectivity as assess by functional Magnetic Resonance Imaging (fMRI) may be a promising biomarker to be used for trials of disease modifying treatment. In particular, fMRI may of special interest to assess disease progression in HD subjects in the pre-manifest stage who do not have symptoms clinically. Question: Is cortico-striatal functional connectivity in HD as assessed by fMRI at 7 T a biomarker for disease progression? Method: We assessed 24 pre-manifest HD subjects, 12 manifest HD subjects as well as 16 healthy controls at baseline. 13 HD subjects (9 in the pre-manifest stage of HD) and 8 healthy controls participated in a one year follow-up study. The functional connectivity between the striatum and several cortical areas were analysis. Two tailed t-test was applied. ANOVA was used for the analysis of the one year follow-up data with group as between-subjects factor and time as within-subjects factor. Results: Functional connectivity between striatum and supplementary motor area was impaired comparing manifest HD subjects with controls ( p = 0.01) and premanifest HD subjects with controls ( p = 0.03) at baseline. At the one year follow-up, functional connectivity between striatum and premotor area was impaired comparing manifest HD subjects with controls (group p = 0.002, time p = 0.04, group by time p = 0.02). Likewise, premanifest HD subjects showed decline compared to control subjects over time (group p < 0.001, time p = 0.002, group by time p = 0.001). Interestingly, HD subjects in the pre-manifest stage who are more than 8 years away to calculated motor symptom onset also showed impairment of functional connectivity compared to controls (group p = 0.001, time p = 0.003, group by time p = 0.002). Conclusion: These data indicate progressive impairment of functional connectivity between striatum and premotor area in HD subjects. Assessment of cortico-striatal functional connectivity by fMRI is a promising biomarker to assess disease progression including the premanifest stage of HD, when subjects do not have symptoms.